Development of a Psycho-Emotional Empowerment Training Package Based on the Lived Experiences of Single-Parent Adolescent Boys and Its Effectiveness on Parent-Child Interaction - Shams, Zahra; Sedrpoushan, Najmeh; Dehghan, Marieh (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2024)
Objective: This study aimed to develop a psycho-emotional empowerment training package based on the lived experiences of single-parent adolescent boys and to examine its effectiveness on parent-child interaction. Methods and Materials: The research method was qualitative, phenomenological-descriptive, and the method for the quantitative part was a quasi-experimental design with a pre-test, post-test, control group, and a two-month follow-up period. The statistical population included single-parent adolescent boys studying in the first secondary school level in Abadeh city during the 2023-2022 academic year. The qualitative sample consisted of 15 single-parent adolescent boys selected through purposive sampling and subjected to in-depth interviews. The quantitative sample included 35 single-parent adolescent boys selected through purposive sampling and randomly assigned to experimental and control groups (18 adolescents in the experimental group and 17 adolescents in the control group). The adolescents in the experimental group received the psycho-emotional empowerment training package over 10 weeks in 10 90-minute sessions. The pre-test was conducted before the intervention, the post-test was conducted after the intervention, and the follow-up phase was conducted two months later. The questionnaire used in this study was the Parent-Child Interaction Questionnaire (Fine, Moreland, & Schwebel, 1983). Data obtained from the study were analyzed using mixed analysis of variance with SPSS23 statistical software. Findings: The results indicated that the psycho-emotional empowerment training package had sufficient content validity according to experts. Additionally, this training package had an impact on parent-child interaction (P<0.001; Eta=0.64; F=56.98) among single-parent adolescent boys. Conclusion: Based on the study’s findings, it can be concluded that the psycho-emotional empowerment training package, by creating emotional competencies, gaining competence, autonomy, effectiveness, and establishing connections with others, empathy, and kind behavior towards others, can be used as an effective method to improve parent-child interaction in single-parent adolescent boys.